Specificity and the macroeconomics of restructuring - Caballero, Ricardo J. (Yrjö Jahnsson lectures., 2007)
A proposal that the notion of specificity-the idea that factors of production are not interchangeable-can provide a unified framework to analyze and understand a wide variety of macroeconomic phenomena stemming from the transactional environment and micro.